Application and Efficacy of Melatonin Elastic Liposomes in Photoaging Mice. (8th March 2022) - Hou, Xueqin; Qiu, Xinyu; Wang, Yaping; Song, Shuangshuang; Cong, Yifan; Hao, Jifu
Abstract : Transdermal drug delivery system is a preferable choice to overcome the low bioavailability of oral medication. Elastic liposomes have shown great effectiveness for percutaneous transport of melatonin (MLT). In this study, the elastic liposomes loaded with MLT were prepared using thin-film dispersion method and optimized through the central composite design (CCD) approach. The physicochemical properties and skin permeation against UV-induced skin photoaging efficacy of the developed MLT-ELs were assessed. The average size of the MLT-ELs was about 49 nm with a spherical shape and high encapsulation efficiency (73.91%) and drug loading (9.92%). The results of FTIR, DSC, and XRD revealed that the chemical structure of MLT was not changed after prepared elastic liposomes, and the drug was successfully encapsulated in the elastic liposome membrane material. In vitro skin permeation evaluation showed that the cumulative penetration of elastic liposomes was 1.5 times higher than that of conventional liposomes, highlighting that the elastic liposomes more easily penetrated into the body. The photoaging experiment results indicated that topical MLT-EL treatment ameliorated the skin elasticity, enhanced the skin hydration level, and preserved the integrity of dermal collagen and elastic fibers. It could be concluded that the elastic liposomes might serve as a promising platform for the transdermal delivery of melatonin.